Efficient and Facile One-Pot Synthesis of Novel Benzimidazoles using Rice Husk (Global Journal of Science Frontier Research, 2020)
New and facile one-pot approach for the synthesis of substituted benzimidazoles from the reaction of substituted benzaldehyde and o-phenylenediamine room temperature using Rice Husk Ash: CaCl 2 (RHA:CaCl 2 ) as a green catalyst was presented in the paper. After the completion of the reaction, the reaction mixture was poured into ice-coldwater with stirring, and the precipitated product was filtered using the filter pump. The crude product was then recrystallized from ethanol to give analytically pure samples in good to excellent yield. The purity of compounds were characterized by melting point and thin-layer chromatography. The synthesized compounds were characterized by using 1 HNMR and FTIR spectral techniques. Metal-free, short reaction time, high yields, mild reaction condition, simple work-up, high atom economy, cost-effectiveness, and no need for column purification are some beauties of this methodology.
Keywords: rice husk; green catalyst; benzimidazole; metal-free; atom economy